Foreign bank ownership and business cycle synchronization in the European Union - Borowski, Jakub; Czerniak, Adam; Boratyński, Jakub; Rosati, Dariusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
In this article the impact of foreign bank ownership on the synchronization of business cycles between the euro area and EU countries is analysed with the use of data for 28 EU member states from 1998 to 2016. The main finding is that economies with a higher share of assets owned by foreign banks are more cyclically synchronized with the euro area which is chiefly the result of greater alignment in investment cycles. It suggests that foreign banks, originated mainly in other EU member states, treat host countries largely as an extension of their domestic markets, and their lending behaviour at home and in the host countries is similar. Our results show that greater foreign bank ownership reduces the costs of European monetary integration
Argumenta Oeconomica, 2020, Nr 1 (44), s. 19-46